"CF asthma": what is it and what do we do about it?. Issue 8 (1st August 2002) - Balfour-Lynn, I M; Elborn, J S
Abstract : The diagnosis of "CF asthma" is problematic and it is difficult to determine which patients have a combination of CF and asthma and which have asthma like symptoms caused by inflammation of the CF lung. This may not matter, however; the relevance lies in the possible approaches to treatment.